HUBUNGAN DAYA LEDAK OTOT TUNGKAI TERHADAP HASIL SMASH ATLET BOLA VOLI JUNIOR PUTRA TRI WIJAYA DIESEL PEKANBARU - M. Zam Zami; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observation that writer did to club volleyball junior son of TRIWIJAYA DIESEL , precisely in the field TRI WIJAYA DIESEL at Kapau Sari 9 Pekanbaru. Writer found some troubles on the club volleyball junior TRI WIJAYA DIESEL at their smash , when an athlete to smash the ball over the net often do not produce point so it fails. The goal to be achieved in this research is to find the explosive power limb muscles on the smash athletes volleyball junior son of TRI WIJAYA DIESEL Pekanbaru. Of the population is an athlete volleyball junior son of TRI WIJAYA DIESEL Pekanbaru amounting to 12 the athletes. Included in this research as many as 12 sons athletes volleyball junior son of TRI WIJAYA DIESEL Pekanbaru using the techniques of sampling. The research is vertical synchronization intrumen power jump smash and the results of tests . Based on the results of the research that the writer has described in the piblished chapter, so the following conclusions may be drawn from the results: Leg muscle explosive power have no relationship to the smash on the volleyball junior son of TRI WIJAYA DIESEL Pekanbaru.Key Words: Leg muscle explosive power, volleyball smash results